Home blood pressure monitoring, secure electronic messaging and medication intensification for improving hypertension control - Ralston, J.D.; Cook, A.J.; Anderson, M.L.; Catz, S.L.; Fishman, P.A.; Carlson, J.; Johnson, R.; Green, B.B. (Applied Clinical Informatics, 2014)
Objective: We evaluated the role of home monitoring, communication with pharmacists, medication intensification, medication adherence and lifestyle factors in contributing to the effectiveness of an intervention to improve blood pressure control in patients with uncontrolled essential hypertension.Methods: We performed a mediation analysis of a published randomized trial based on the Chronic Care Model delivered over a secure patient website from June 2005 to December 2007. Study arms analyzed included usual care with a home blood pressure monitor and usual care with home blood pressure monitor and web-based pharmacist care. Mediator measures included secure messaging and telephone encounters; home blood pressure monitoring; medications intensification and adherence and lifestyle factors. Overall fidelity to the Chronic Care Model was assessed with the Patient Assessment of Chronic Care (PACIC) instrument. The primary outcome was percent of participants with blood pressure (BP) <140/90 mm Hg.Results: At 12 months follow-up, patients in the web-based pharmacist care group were more likely to have BP <140/90 mm Hg (55%) compared to patients in the group with home blood pressure monitors only (37%) (p = 0.001). Home blood pressure monitoring accounted for 30.3% of the intervention effect, secure electronic messaging accounted for 96%, and medication intensification for 29.3%. Medication adherence and self-report of fruit and vegetable intake and weight change were not different between the two study groups. The PACIC score accounted for 22.0 % of the main intervention effect.Conclusions: The effect of web-based pharmacist care on improved blood pressure control was explained in part through a combination of home blood pressure monitoring, secure messaging, and antihypertensive medication intensification.Citation: Ralston JD, Cook AJ, Anderson ML, Catz SL, Fishman PA, Carlson J, Johnson R, Green BB. Home blood pressure monitoring, secure electronic messaging and medication intensification for improving hypertension control: a mediation analysis. Appl Clin Inf 2014; 5: 232–248 http://dx.doi.org/10.4338/ACI-2013-10-RA-0079
Keywords: Personal health records; patient-provider communication; telemedicine and telehealth; remote monitoring; internet portal; patient self-care; home care and e-health